Tracking Employment Conditions and Satisfaction of Graduate Users of the Department of Information Science, Rajabhat Mahasarakham University Graduated During the Academic Year 2018 - 2020 - Suebsunthone, Jenjira; Nammungkhun, Nantana; Supawat, Nukanda (Chophayom Journal, 2023)
The purposes of the current study were 1) to study the employment status of the information science major graduates who graduated from the 2019-2021 academic year in the Faculty of Humanities and Social Sciences, Rajabhat Maha Sarakham University, and 2) to study employers’ satisfaction with the bachelors who graduated from the 2019-2021 academic years in the Faculty of Humanities and Social Sciences, Rajabhat Maha Sarakham University. The samples were 32 bachelor degree graduates and 18 employers. The instrument was a questionnaire, and the statistics used in data collection were percentages, mean scores, and standard deviation. The results of the study were as follows. 1) In terms of employment status, it was found that the majority of the bachelors who graduated from the 2019-2021 academic years were employed after graduating (78.13%). Most graduates who are employed in private sectors (50%), government units (33.33%), other careers (11.11%), and own businesses (5.56%). 2) In terms of satisfaction, it was found that the employers were satisfied with the working quality and characteristics of the graduates at a very high level overall ( = 4.58). Specifically, the employers were satisfied with the ethics ( = 4.70), interpersonal relationship skills, and responsibility ( = 4.59), numerical analysis, communication, and information technology skills ( = 4.56), knowledge ( = 4.54), and cognitive skills ( = 4.48), respectively. Keywords: Employment status, Satisfaction, Employers